Correct Answers with Wrong Justifications? Analysis of Explanations in Classical Mechanics with Fci Test - Hernandez-Silva, C; Tecpan-Flores, S (Institute of Physics Publishing, 2018)
This study presents the results of an analysis of the explanations constructed by future physics teachers about their chosen answers in a conceptual test in classic mechanics. Additionally, to selecting a multiple-choice answer in the Force Conceptual Inventory test [1] the teachers were required to give an explanation for their answers in order to determine the relationship between their level of conceptual knowledge and the quality of the explanations they gave using this knowledge. The results suggest that the 28 participants have difficulties in constructing adequate physical explanations. They suggest too that they have deficiencies in the development of their scientific thinking skills and in the use of their prior knowledge. We propose indicators for the construction of explanations in physics and we discuss the implications for the initial formation of physics teachers. © Published under licence by IOP Publishing Ltd.